Values and Politics in the US: An Equilibrium Analysis of the 2004 Election - Woojin Lee; John Roemer (University of Massachusetts, Department of Economics, 2005)
The CNN exit polls after the 2004 election rated moral values the most important issue; next came jobs and the economy. Eighty percent of the voters who rated moral values the most important issue voted for Bush while eighty percent of the voters who rated jobs and the economy the most important voted for Kerry. We study the extent to which the distribution of voter opinion on moral values influences the positions that parties take on the economic issue, which we take to be the size of the public sector, through political competition. There are at least two distinct ways this influence might occur. First, because the Republican Party is identified with a traditionalist stance on moral values, some voters who desire a large public sector may nevertheless vote Republican because traditionalist morality is important for them. This we call the policy bundle effect. Second, it may be the case that those who subscribe to a traditionalist morality take economic conservatism to be part of that view, in the sense that they view the state as, for instance, usurping the role of the individual and/or family. We call this effect the moral Puritanism effect. Thus economic conservatism in the US may be politically strengthened by moral traditionalism because the Republican Party links the two issues (policy bundle) or because moral traditionalists in the US are anti-statist (in the Puritan sense). Our analysis will enable us to predict how equilibrium policies proposed by Democratic and Republican Parties would change if all voters had the same view on the moral-values issue, and we will decompose these changes into the aforementioned two effects. JEL Categories: D3, D7, H2
Keywords: 330; moral values; redistribution; moral Puritanism effect; policy bundle effect; party unanimity Nash equilibrium